Gender and age related differences in leg stiffness and reactive strength in adolescent team sports players - Lehnert, M.; De Ste Croix, M.; Svoboda, Z.; Elfmark, M.; Sikora, O.; Stastny, P. (Journal of Human Kinetics, 2020)
The aim of the present study was to identify potential gender differences in leg stiffness and reactive strength during hopping tasks in 13 to16-year old team sports players. Reactive strength index (RSI) and leg stiffness were obtained in two consecutive seasons from 51 girls (U14: n = 31, U16: n = 20) and 65 boys (U14: n = 32, U16: n = 33). A significant main effect on absolute (U14: p = 0.022, Eta²= 0.084; U16: p < 0.001, Eta²= 0.224) and relative leg stiffness (U14 p<0.001; Eta²= 0.195; U16; p = 0.008, Eta²= 0.128) for gender was found in both groups with values higher in boys than in girls. For absolute and relative stiffness gender differences in the U14 group were significant in the 1st year only (p=0.027 and p=0.001), and for the U16s in the 2nd year only (p < 0.001 and p = 0.022). For RSI, a significant main effect for gender was observed in the U16 group only (p < 0.001 Eta²= 0.429) with values significantly higher in boys than in girls in both years of measurement (p = 0.001; p < 0.001). Results of this study support previous limited findings, mostly related to non-athletes, suggesting lower stretch-shortening cycle capability in adolescence female compared to male, however our data only partly supports the theory that quality of neuromuscular functions increases with age until post puberty.